The Aesthetic Dimension in Popular Topics by Naguib Younes (Al-Academy, 2022)
The aesthetic dimension in popular subjects is one of the important topics in the history and culture of peoples, as it is the vessel from which their faith, traditions, original values, language, ideas, practices and way of life are derived, which expresses their culture and national identity, and it is the bridge of communication between generations throughout the ages.It is one of the main pillars in the process of development and development, and popular subjects have special images related to real daily life, and they are the best source for man to narrate through him in his portrayal of daily life in general, and for the artist in particular, who is part of this daily life and its vocabulary, as he interacts with it so that he can represent it aesthetically with creative works Hence the research problem arises for us by asking the following question: Did the aesthetic dimension appear in the popular subjects in the paintings of the artist Naguib Younes? Was the artist Naguib Younis according to the depiction of popular subjects in his paintings